Omvärldsanpassning inom ideell sektor - Alonso, Sebastian (2010)
Over the last few years, many non-governmental organizations (NGOs) in the aid sector have grown and become important economic, social and political actors in Sweden. However this sector has also been hard criticized in terms of aid effectiveness. Church of Sweden (CoS), a well established organization in this sector, has faced new challenges in form of demands from their environment regarding reporting aid work. These demands have pushed the International Department of Church of Sweden into a process for adapting the structure in order to meet the new effectiveness requirements.